On the Limits of Trust: Characterising Automated Teller Machine Fraudsters in Southwest Nigeria (2016)
Purpose – This paper aims to investigate automated teller machine (ATM) fraud in southwest Nigeria, as extant studies have not examined the unintended consequences of ATM subscription particularly the effect of the identity of fraudsters and the strategies for defrauding. Design/methodology/approach – Using sequential exploratory strand of mixed method, data were collected from both ATM users and victims of ATM fraud using multi-stage sampling procedure. This involved purposive selection of Lagos and Oyo states. Findings – Results showed that fraudsters were typically lovers, friends, relatives and sometimes children of victims. Strategies for defrauding included card cloning, swapping of cards and physical attacks at ATM galleries. Research limitations/implications – Because of the size of the sample which is small, the research results may lack generalizability. More expansive works are needed across Nigeria in this regard. Practical implications – The paper includes implications for policy initiative concerning the deployment and use of payment systems such as ATM in Nigeria. Social implications – The paper reveals the limits of trust in cashless policy. It raises salient policy issues concerning the need for the governance of trust to engender adoption. Originality/value – The paper characterizes fraudsters and their strategies for defrauding.